Does Damage from Natural Disaster Affect Child Labor? Evidence from Indonesia - Sulistyo, Tito; Syafitri, Wildan (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2021)
Disasters, both natural and non-natural, can cause a severe impact on every life aspects in a country, including the economic aspect. In Indonesia, as a reaction of deteriorating economic conditions caused by disasters, households are often forced to adjust the declining of their real income by taking out their children from school thereby they can send them to work as a household buffer to shocks. This paper aims to analyze the impact of the natural disaster damage on the number of child labor and the differences of these impacts between urban and rural areas. By using cross section data from the fifth wave Indonesia Family Life Survey collected in 2014, we find that there is a positive relation between the natural disaster damage and the number of child labor, and then a significant difference between impacts in urban and rural areas. Policy implications of the findings are provided.